2018
DOI: 10.1016/j.physletb.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric cumulants as a probe of the proton substructure at LHC energies

Abstract: We present a systematic study of the normalized symmetric cumulants, NSC(n,m), at the eccentricity level in proton-proton interactions at √ s = 13 TeV within a wounded hot spot approach. We focus our attention on the influence of spatial correlations between the proton constituents, in our case gluonic hot spots, on this observable. We notice that the presence of short-range repulsive correlations between the hot spots systematically decreases the values of NSC(2,3) and NSC(2,4) in midto ultra-central collisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 37 publications
(113 reference statements)
2
41
0
Order By: Relevance
“…Adding the contributions of Eqs. (20), (21) and (22), one obtains: The expression of c n {4} coincides with that derived in [7] for n = 2, and then extended in [8] to n = 3. The result for SC(3, 2) is new.…”
Section: B Identical Pointlike Sourcessupporting
confidence: 67%
See 3 more Smart Citations
“…Adding the contributions of Eqs. (20), (21) and (22), one obtains: The expression of c n {4} coincides with that derived in [7] for n = 2, and then extended in [8] to n = 3. The result for SC(3, 2) is new.…”
Section: B Identical Pointlike Sourcessupporting
confidence: 67%
“…(14). It is directly proportional to the 3-point function of the density field C 3 , as the contribution (21) to the kurtosises. For identical pointlike sources, Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would increase the total and elastic cross sections at low √ s, while the effect at higher √ s could be tuned away by a slightly smaller value of r max or α s . Other studies of proton substructure [71] has indicated that the number of hot-spots required for a satisfactory qualitative description -25 - of LHC data is larger than three, but at the same time, previous studies of the Mueller dipole formalism in the DIPSY event generator [61] indicated that a triangle configuration of initial dipoles is the most suitable choice for a good description of the cross sections. A study of this sort will therefore likely have to rely on attemps of simultaneous description of both sub-structure and cross sections, and will be referred to a future study.…”
Section: Results For Ppmentioning
confidence: 99%